A prosódia na interação entre afásicos - Santos, Izabelly Correia dos (2012)
Aphasia is considered a reduction and dysfunction of the use of language in which there is a change of language mechanisms at all levels, manifesting itself in both productive and receptive aspects of oral language and/or writing. Facing these characteristics, the speech of aphasics became our object of study by focusing on the prosodic elements and intonation patterns present in them. The assumption used in this work is that the tonal choices, which are being made along the interaction, are responsible for the construction of a context, and the tonal prominence options will build the sense of the text simultaneously. The interactive context suggests the recognition that the behavior of prosodic behaviour constructs a significant intonation outline, being interpreted by the listener as incorporation of an informational content, but at the same time can provide clues regarding interactivity marks, while keeping the proximity/distance between the interlocutors, associated with typical patterns (referring tones) in reference to the prior knowledge shared or new information (proclaiming tones). This work sought to identify intonation patterns and other prosodic resources domains present in the oral organization of the subjects participation in the Conviviality Group for Aphasics. Aware of this, we observed recurring prosodic elements, the use of other linguistic resources and the role of intonation tracks for the constitution of meaning. To achieve the proposed objective, reading workshops were held with six aphasic subjects, of both genders, who participated and attended regularly the Conviviality Group for Aphasics, Catholic University of Pernambuco, during four meetings. The studies on the theme presented grounded the research on the organization of oral speech of aphasics, highlighting the prosodic relationship, from the perspective of Brazil (1985). It is concluded that, over the interactional process, prosody was common in the construction of speech of the analyzed subjects in this research, who constantly resorted to paralinguistic resources and proclamation tone, the most recurrent function, which serves as an intonation trace and is related to the new knowledge. The relevance of the work lies in thinking of the aphasic subject as producer of a speech that makes use of paralinguistic resources and prosodic patterns to understand and be understood